Increased thrombin generation in kidney transplant recipients with donor-specific antibodies directed against human leukocyte antigens - Linda Lóczi; Linda Lóczi; Réka P. Szabó; Rita Orbán-Kálmándi; Rebeka Hodossy-Takács; Anikó Szilvási; Zoltán Szalai; Gábor Nagy; Péter Antal-Szalmás; Balázs Nemes; Zsuzsa Bagoly; Zsuzsa Bagoly; et al. (Frontiers in Immunology)
IntroductionThe development of de novo anti-HLA donor specific antibodies (DSAs) is associated with poor outcomes in kidney transplant recipients. It is surmised that an interaction between DSAs and the graft endothelium cause tissue injury, however, the exact underlying pathomechanism and optimal management of patients with DSAs remain undetermined.AimsWe hypothesized that in kidney transplant recipients the presence of DSAs induce hemostasis alterations, including hypercoagulability, as assessed by the thrombin generation assay (TGA). Patients and methods. In this observational cohort study, 27 kidney transplant recipients with DSAs (DSA+ group) and 16 without DSAs (DSA– group) were enrolled. Venous blood samples were obtained, and besides routine laboratory tests, von Willebrand factor antigen (VWF), FVIII activity, soluble E selectin (sEsel), soluble P selectin (sPsel), TGA, clot lysis assay (CLA), complement levels (C3, C4) were measured. To correlate results with potential changes in DSA status over time, patients were followed and reassessed 6 ± 1.5 months later.ResultsVWF and sPsel did not differ between groups, but both parameters were increased in the majority of patients. Endogenous thrombin potential (ETP) was significantly higher in the DSA+ group as compared to DSA– patients (median:1666; IQR:1438-2012 vs. 1230; IQR:1097-1659 nM*min, p=0.0019). Follow-up measurements indicated that the observed hemostasis alterations were not transient. CLA parameters, C3 and C4 did not differ between DSA+ and DSA– groups. The extent of anti-HLA II DSA positivity correlated positively with ETP, while tacrolimus levels negatively correlated with ETP and VWF/FVIII levels.ConclusionsIn patients with anti-HLA class II DSAs, thrombin generation was significantly increased as compared to DSA– kidney transplant recipients, suggesting that the presence of antibodies is associated with hypercoagulability. Tacrolimus levels were negatively associated with TGA parameters. Hypercoagulability, associated with the presence of DSAs, may potentially contribute to the pathomechanism of antibody-mediated graft injury, warranting future prospective studies.